Penyelesaian Gugatan Sederhana Melalui E-court Pasca Diundangkannya Perma 7 Tahun 2022 - Tambunan, Jonathan Hiero; Yunanto, Yunanto (Program Studi Magister Kenotariatan, Fakultas Hukum, Universitas Diponegoro, 2024)
ABSTRACTSupreme Court Regulation (Perma) Number 7 of 2022 amends Perma Number 1 of 2019 on the Administration of Cases and Trials Electronically, providing an alternative mechanism for simple lawsuits involving breach of contract and unlawful acts. This study examines the summons of simple lawsuit cases filed electronically through the E-court system and the duration of the objection process. Using a normative juridical method with a statutory approach, the research is descriptive-analytical and relies on secondary data. The findings reveal differences in summons procedures and notifications between Perma Number 4 of 2019 and Perma Number 7 of 2022, including ambiguities in the definitions of working days and calendar days. Legal certainty and protection are crucial in resolving simple lawsuits through E-court following the enactment of Perma Number 7 of 2022.Keywords: Settlement; Simple Lawsuit; E-Court.ABSTRAKPeraturan Mahkamah Agung (Perma) Nomor 7 Tahun 2022 mengubah Perma Nomor 1 Tahun 2019 tentang Administrasi Perkara dan Persidangan secara Elektronik, menyediakan mekanisme alternatif untuk gugatan sederhana terkait wanprestasi dan perbuatan melawan hukum. Penelitian ini membahas panggilan perkara gugatan sederhana yang didaftarkan secara elektronik melalui E-court serta durasi proses pengajuan keberatan. Menggunakan metode yuridis normatif dengan pendekatan peraturan perundang-undangan, penelitian ini bersifat deskriptif analitis dan menggunakan data sekunder. Hasilnya menunjukkan perbedaan tata cara panggilan dan pemberitahuan pada Perma Nomor 4 Tahun 2019 dan Perma Nomor 7 Tahun 2022, termasuk ambiguitas definisi hari kerja dan kalender. Kepastian dan perlindungan hukum menjadi esensial dalam penyelesaian gugatan sederhana melalui E-court pasca diundangkannya Perma Nomor 7 Tahun 2022.Kata Kunci : Panyelesaian; Gugatan Sederhana; E-Court